Memanfaatkan Data Mining danKnowledge Management System Untuk Mengoptimalkan Strategi Pemasaran pada Bank - ARDIJAN HANDIJONO (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2017)
Many large companies store data for a long time, the data need to be stored growing increasingly large. This is commonly referred to as the Data Explosion. Likewise occurred in the banking world. Many Bank store huge data, but only got a little benefit  (Beath, 2012). Data Mining as a powerful tool in Business Intelligence can be used to find the hidden proficiency level information, especially information that supports decision in determining the marketing strategy(Sun, 2008). With the Data Mining, the company can run a Knowledge Based Marketing strategy (Shaw, 2001). To store Knowledge were found by Data Mining, so it needed a system that could manage the Knowledge systematically using Knowledge Management System. even with the Knowledge of the system can be distributed with the DM Collaboration  (Uriarte, 2008). With the construction of a Knowledge Management system which integrated with Data Mining, the company can meet the needs of lifelong learning, enhance the effectiveness of theuse of Knowledge, as well as reducing the possibility of loss of Knowledge. (ard.)